IMPLEMENTATION OF AUGMENTED REALITY LEARNING MEDIA IN ARABIC LANGUAGE COURSES - Amrulloh, Moh Ajib (Kitaba, 2024)
Books are the most frequently used media by teachers. However, teachers often face difficulties in explaining shapes or depicting the real appearance of objects and sometimes get caught up in merely memorizing terms. Therefore, there is a need for media that can assist both teachers and students in the learning process. The aim of this study is to determine the product specifications, attractiveness, and practicality of augmented reality learning media in discovery learning activities for the Arabic language subject, specifically the living room material, for sixth-grade students at Madrasah Ibtidaiyah Miftahul Huda Kepung, Kediri. This study employs a qualitative research method, which generates descriptive data in the form of written or spoken words from observed sources. The qualitative descriptive method describes research in a more specific, in-depth, and transparent manner to obtain more accurate and reliable data from direct sources, which are then summarized into conclusions and linked with existing theories to achieve more accurate research results. The research was conducted at Madrasah Ibtidaiyah Miftahul Huda Kepung, Kediri. The results of this study indicate that the product's attractiveness level is 86.06% and the practicality level is 88.64%. These results deem the product suitable and feasible as a new learning media for the living room material.